Therapeutic responses to antimalarial and antibacterial drugs in vivax malaria. - Pukrittayakamee, S; Imwong, M; Looareesuwan, S; White, N (2004)
Plasmodium vivax is the most prevalent malaria infection and is an important cause of morbidity in Central and South America and Asia. P. vivax is generally sensitive to the common antimalarial drugs but high level resistance to chloroquine and/or pyrimethamine has been documented in some geographic locations. In the studies reviewed here, the therapeutic responses to antimalarial and antibacterial drugs in vivax malaria have been assessed in the Bangkok Hospital for Tropical Diseases. The evaluated drugs consisted of the eight most widely used antimalarial drugs and anti-bacterial drugs that possess antimalarial activities (tetracycline, doxycycline, clindamycin or azithromycin). The activities of these drugs in descending order of parasite clearance times were artesunate, artemether, chloroquine, mefloquine, quinine, halofantrine, primaquine, followed by the antibacterial drugs and lastly sulfadoxine-pyrimethamine. Clinical responses to sulfadoxine-pyrimethamine were also poor with evidence of high grade resistance in 42% of the patients. Of the four antibacterial drugs, clindamycin was more effective than azithromycin and can be an alternative to the tetracyclines. Except for chloroquine and mefloquine which have long plasma half lives and may therefore suppress first relapses, the cumulative cure rates for the short acting antimalarial drugs were similar. Double infection with Plasmodium falciparum was common and usually manifested 3-4 weeks following clearance of vivax malaria. The prevalence of cryptic falciparum malaria was 8-15% and was higher in patients treated with less potent antimalarial drugs. Follow-up studies have revealed that the relapse time in Thai patients with vivax malaria is on average only 3 weeks, but can be suppressed by the slowly eliminated antimalarial drugs such as chloroquine and mefloquine. For accurate comparison of relapse/recrudescence rates in vivax malaria, at least 2 month's follow-up is required. It can be concluded that in malarious areas of Thailand, double infection with P. falciparum and P. vivax is common affecting at least 25% of the patients and usually manifests as sequential illnesses. P. vivax in Thailand is sensitive to chloroquine but has acquired high grade resistance to sulfadoxine-pyrimethamine.